2015
DOI: 10.4103/2008-7802.156267
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-based education and counseling to reduce stress among patients with diabetes mellitus attending a tertiary care hospital of India

Abstract: Background:Stress among diabetic patients is much more as compared to normal individuals. A delayed recognition of stress undoubtedly worsens the prognosis for survival for many diabetic patients. Hence, this study was planned to develop an intervention model for the reduction of stress among diabetic patients and to evaluate the developed intervention model in the proposed group.Methods:This study was conducted in endocrinology outpatient department of a tertiary care hospital. Starting at random, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Current studies on stress reduction interventions in patients with diabetes show that there are noninvasive methods to significantly decrease stress, including educational sessions and cognitive-behavior therapy. [55][56][57] Furthermore, teaching mindfulness stress reduction in patients with severe cases of diabetes significantly reduced cardiovascular risk factors. 58 To our knowledge there is limited research on interventions focused on decreasing stress in relation to perceived discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on stress reduction interventions in patients with diabetes show that there are noninvasive methods to significantly decrease stress, including educational sessions and cognitive-behavior therapy. [55][56][57] Furthermore, teaching mindfulness stress reduction in patients with severe cases of diabetes significantly reduced cardiovascular risk factors. 58 To our knowledge there is limited research on interventions focused on decreasing stress in relation to perceived discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…However, utilization of these digital resources in the field of health care in general and mental health care in particular are very low. Literature shows only a handful of projects that deliver mobile based services for health information [ 38 , 39 ], HIV [ 40 , 41 ], diabetes [ 42 ], tuberculosis [ 43 ], cardiovascular diseases [ 44 , 45 ] in India, and only two SMS services for mental health issues [ 46 , 47 ]. To the best of our knowledge, no research from India highlights the use of app based intervention for mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other mHealth studies reported on Diabetes concentrated mainly on Client education and behaviour change (BCC). [13][14][15][16] The strength of our study were, barriers to access to healthcare services were minimum, the maximum radial commute distance to the health care facility from the furthest located households (within the gram panchayat revenue boundaries) was 1 km. All the services were offered under universal health coverage policy and hence out of pocket expenditure to all the healthcare seekers was zero.…”
Section: Discussionmentioning
confidence: 97%